1999
DOI: 10.1074/jbc.274.2.889
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of γ-Aminobutyric Acid (GABA) Transporters by Extracellular GABA

Abstract: ␥-Aminobutyric acid (GABA) transporters on neurons and glia at or near the synapse function to remove GABA from the synaptic cleft. Recent evidence suggests that GABA transporter function can be regulated, although the initial triggers for such regulation are not known. One hypothesis is that transporter function is modulated by extracellular GABA concentration, thus providing a feedback mechanism for the control of neurotransmitter levels at the synapse. To test this hypothesis, GABA uptake assays were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 41 publications
4
100
2
Order By: Relevance
“…Transporter substrates are known to regulate transporter function and expression (Bernstein and Quick, 1999;Duan et al, 1999;Ramamoorthy and Blakely, 1999;Munir et al, 2000;Chi and Reith, 2003). The present study demonstrates that a SERT substrate, D-amphetamine, increases SERT basal phosphorylation that is sensitive to p38 MAPK inhibition, suggesting that constitutively active p38 MAPK regulates SERT substrate effects on SERT phosphorylation; however, we cannot rule out a possible influence of monoamines released from synaptosomes by D-amphetamine on SERT basal phosphorylation.…”
Section: Discussionmentioning
confidence: 54%
“…Transporter substrates are known to regulate transporter function and expression (Bernstein and Quick, 1999;Duan et al, 1999;Ramamoorthy and Blakely, 1999;Munir et al, 2000;Chi and Reith, 2003). The present study demonstrates that a SERT substrate, D-amphetamine, increases SERT basal phosphorylation that is sensitive to p38 MAPK inhibition, suggesting that constitutively active p38 MAPK regulates SERT substrate effects on SERT phosphorylation; however, we cannot rule out a possible influence of monoamines released from synaptosomes by D-amphetamine on SERT basal phosphorylation.…”
Section: Discussionmentioning
confidence: 54%
“…A previous study has revealed that chronic exposure of cultured astrocytes to the antagonist of γ-aminobutyric acid (GABA) transporters increases the expression of GABA transporters (Bernstein and Quick, 1999). This raises the possibility that chronic blockade of GLT-1 with DHK for 60-70 min would increase the expression of GLT-1, and hence would result in the greater release of Glu during OGD 24 h later via reversed operation of GLT-1.…”
Section: Resultsmentioning
confidence: 99%
“…The transport assay was carried out essentially as described before (Bernstein and Quick 1999). In brief the vector-transfected HEK 293 cells and pBK-serta transfectants were grown until they were confluent.…”
Section: Transport Assaymentioning
confidence: 99%